Facial emotional expression in reaction to social exclusion in borderline personality disorder - Stäbler, Katja; Stopsack, Malte; Fiedler, Peter (Psychological medicine, 2011)
Background: Disturbances in social interaction are a defining feature of patients with borderline personality disorder (BPD). In this study, facial emotional expressions, which are crucial for adaptive interactions in social contexts, were assessed in patients with BPD in response to social exclusion. Method: We examined facial emotional reactions of 35 patients with BPD and 33 healthy controls when playing Cyberball, a virtual ball-tossing game that reliably induces social exclusion. Besides self-reported emotional responses, facial emotional expressions were analyzed by applying the Emotional Facial Action Coding System (EMFACS). Results: Patients with BPD showed a biased perception of participation. They more readily reported feeling excluded compared to controls even when they were included. In BPD, social exclusion led to an increase in self-reported other-focused negative emotions. Overall, EMFACS analyses revealed that BPD patients reacted with fewer positive expressions and with significantly more mixed emotional expressions (two emotional facial expressions at the same time) compared to the healthy control group when excluded. Conclusions: Besides a negative bias for perceived social participation, ambiguous facial emotional expressions may play an important role in the disturbed relatedness in patients with BPD.
Gesehen am 21.06.2021